2015
DOI: 10.1007/s12325-015-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine and Bisoprolol on Doppler-derived Coronary Flow Velocity Reserve in Patients with Stable Coronary Artery Disease: Beyond the Heart Rate

Abstract: IntroductionCoronary flow velocity reserve (CFVR) is an important prognostic marker in patients with stable coronary artery disease (CAD). Beta-blockers and ivabradine have been shown to improve CFVR in patients with stable CAD, but their effects were never compared. The aim of the current study was to compare the effects of bisoprolol and ivabradine on CFVR in patients with stable CAD.MethodsPatients in sinus rhythm with stable CAD were enrolled in this prospective, randomized, double-blind trial. Patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 47 publications
2
25
0
5
Order By: Relevance
“…In addition, ivabradine increases coronary flow reserve and collateral perfusion, promoting the development of coronary collaterals and maintaining endothelial function in patients with chronic stable angina 47,48 . The antianginal effects of ivabradine have been documented in several randomized clinical trials against placebo, various active comparators, and in addition to β-blockers, as well as in unselected studies reflecting routine clinical practice 29,49 .…”
Section: Key Points For Nicorandilmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ivabradine increases coronary flow reserve and collateral perfusion, promoting the development of coronary collaterals and maintaining endothelial function in patients with chronic stable angina 47,48 . The antianginal effects of ivabradine have been documented in several randomized clinical trials against placebo, various active comparators, and in addition to β-blockers, as well as in unselected studies reflecting routine clinical practice 29,49 .…”
Section: Key Points For Nicorandilmentioning
confidence: 99%
“…Subsequently, in a double-blind, placebo-controlled, crossover study conducted in women with effort angina but no obstructive coronary artery disease, ranolazine produced no significant benefits except in some patients with impaired coronary flow reserve 65 . Analogously, ivabradine has been shown to improve coronary collateral flow and coronary flow reserve in patients with microvascular angina 47,48 . The effects of ivabradine were superior to those of bisoprolol, despite similar degrees of heart-rate reduction 48 .…”
Section: Microvascular Anginamentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of anti-ischemic and antianginal efficacy of ivabradine were first elucidated in experimental studies [5] and confirmed in recent clinical trials. This includes an increase in myocardial diastolic perfusion time [6], enhancement in coronary flow reserve [7], improvement in endothelial function [8], and enhancement in coronary collateral flow in patients with chronic stable coronary artery disease [9]. This makes ivabradine an important antianginal and anti-ischemic therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in contrast to beta-blockers and to non-dihydropyridines calcium antagonists, ivabradine has no negative inotropic or lusitropic effects. Recently, ivabradine has also been shown to increase coronary collateral perfusion and the coronary flow reserve [85-87]. In addition, ivabradine does not unmask α-adrenergic vasoconstriction and, unlike beta-blockers, it maintains the physiological coronary dilation during exercise.…”
Section: Drugs That Reduce Heart Ratementioning
confidence: 99%